Respuesta :

Answer:

54x² - 10x

Step-by-step explanation:

differentiate each term using the power rule

[tex]\frac{d}{dx}[/tex] (a[tex]x^{n}[/tex] ) = na[tex]x^{n-1}[/tex], then

[tex]\frac{d}{dx}[/tex](18x³ - 5x² + 6)

= 3.18[tex]x^{3-1}[/tex] - 2.5[tex]x^{2-1}[/tex] + 0

= 54x² - 10x

Answer:

54x² - 10x

Step-by-step explanation:

differentiate each term using the power rule

\frac{d}{dx}

dx

d

(ax^{n}x

n

) = nax^{n-1}x

n−1

, then

\frac{d}{dx}

dx

d

(18x³ - 5x² + 6)

= 3.18x^{3-1}x

3−1

- 2.5x^{2-1}x

2−1

+ 0

= 54x² - 10x

ACCESS MORE